2003
DOI: 10.1080/00365520310000654
|View full text |Cite
|
Sign up to set email alerts
|

Defining Relapse of Ulcerative Colitis Using a Symptom-based Activity Index

Abstract: HAV interacts with the host signalling mechanism, and HAV VP3, different from HBX and hepatitis C core protein, may activate only SRE-associated intracellular signalling, a pathway associated with cell proliferation and differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
108
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(110 citation statements)
references
References 23 publications
2
108
0
Order By: Relevance
“…We also evaluated the secondary dichotomous endpoint of UC relapse as defined by Jowett et al 29 as an SCCAI of 5 or greater. With use of this definition, six subjects had a clinical relapse in the week after colonoscopy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also evaluated the secondary dichotomous endpoint of UC relapse as defined by Jowett et al 29 as an SCCAI of 5 or greater. With use of this definition, six subjects had a clinical relapse in the week after colonoscopy.…”
Section: Resultsmentioning
confidence: 99%
“…This instrument was developed by Walmsley et al 28 and further validated by Jowett et al 29 in 2003, when a threshold of 5 or more points was defined as a relapse. The SCCAI is a survey of six questions with a point system that measures UC symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Disease activity was monitored by serum YKL-40, CRP, white blood cell count and albumin and the Simple Clinical Colitis Activity Index (SSCAI) [33, 34]. The activity index is based on 5 parameters including number of stools daily, number of stools nightly, presence of blood in the stools, general well-being, and presence of extraintestinal manifestations.…”
Section: Methodsmentioning
confidence: 99%
“…While this has been confirmed in several studies, 62 others have found rather conflicting evidence. 63 Yip and Berman 54 in Egypt report a reduction in OOP payments due to the SHIP; Jowett et al 64 show a reduction in OOP payments for Vietnam's not-for-profit health insurance scheme; and Wagstaff 60 also reports a reduction in OOP payments due to insurance in the government-funded HCFP. Ekman 57 in Jordan also found a reduction in OOP due to insurance; and the risk of financial and catastrophic risks are reduced in Mexico from enrolment in the Seguro Popular scheme.…”
mentioning
confidence: 99%